ANALISA KEBIJAKAN PUBLIK MENGENAI RANCANGAN UNDANG-UNDANG RAHASIA NEGARA - Nuraini, Siti (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2010)
The state secrets bill is very controversial on the one hand, proposed by the government because it is considered very important because it aims "to prevent or deal with things that objectively could threaten the interests of the Unitary Republic of Indonesia." On the other hand the State Secrecy Bill is considered to deviate from the demands for reform to eliminate corruption, collusion and Nepotiosme. Therefore interesting to analyse political and public policy of the State secret Bill.